COMPARATIVE ANALYSIS OF HEMODIALYSIS AND PERITONEAL DIALYSIS IN RENAL FAILURE - Pereira, Heloana Moreno; dos Reis, Kaike Felix; Pereira, Pedro Paulo do Carmo; de Oliveira, Maria Fernanda Vasconcelos; Zamoner, Amanda; Carlos Junior, Marcello Laporta; Viana, Maria Isadora Távora Tavares Cavalcanti; Cabral, Larissa Pacheco; de Alencar, Marília Gabriela Mendes; da Costa, José Eduardo Rocha Siqueira; Osório, Renata Balbino Alves da Silva; Ribeiro, Yohanna Candido; et al. (Seven Editora, 2025)
End-Stage Renal Disease (ESRD) is characterized by the irreversible loss of kidney function, requiring renal replacement therapies such as Hemodialysis (HD) or Peritoneal Dialysis (PD) to maintain patients’ health and quality of life. This systematic review compares HD and PD regarding quality of life, survival outcomes, and cost-effectiveness. A comprehensive search was conducted in PubMed and SciELO databases for studies published between 2014 and 2023, using keywords such as "Peritoneal Dialysis," "Hemodialysis," and "End-Stage Renal Disease." Of the 37 initially identified articles, 15 met the inclusion criteria. Findings indicate that PD improves aspects of quality of life, particularly mental health and the impact of kidney disease, as reported by Zazzeroni et al. (2017). However, HD offers superior control of hemodynamic disturbances, making it preferable for patients with severe comorbidities, such as diabetes and cardiovascular diseases. Regarding survival, studies by Mousavi et al. (2015) and Rigoni et al. (2016) revealed no significant differences in early treatment years, although mortality is higher among diabetic and elderly patients on PD, as highlighted by Yang et al. (2015). Additionally, PD demonstrated greater cost-effectiveness, especially in resource-constrained settings, according to Chang et al. (2016). The review underscores the importance of individualizing treatment decisions based on clinical factors, patient preferences, and available infrastructure. While PD offers advantages in quality of life and cost-effectiveness, HD remains more suitable for patients with severe comorbidities. Further research is needed to refine treatment protocols and improve outcomes for ESRD patients. DOI: https://doi.org/10.56238/sevened2024.037-168